The efficacy of hydroxychloroquine in altering pregnancy outcome in women with antiphospholipid antibodies - Sciascia, Savino; Branch, D. Ware; Levy, Roger A.; Middeldorp, Saskia; Pavord, Sue; Roccatello, Dario; Ruiz-Irastorza, Guillermo; Tincani, Angela; Khamashta, Munther; Schreiber, Karen; Hunt, Beverley J. (Thrombosis and Haemostasis, 2016)
The use of low-dose aspirin and heparinoids has improved the pregnancy outcome in obstetric antiphospholipid syndrome (APS). However, current treatment fails in 20–30 % of APS pregnancies, raising the need to explore other treatments to improve obstetrical outcome. Hydroxychloroquine (HCQ) is widely used in patients with autoimmune diseases, mainly systemic lupus erythematous (SLE), due to its anti-inflammatory, anti-aggregant and immune-regulatory properties. Evidence from in vitro and animal models suggests a potential protective effect of HCQ in obstetric APS. Pending the availability of prospective trials, we aimed to systematically review the available evidence and to assess the clinical judgment of a panel of experts regarding the use of HCQ in improving pregnancy outcome in women with anti-phospholipid antibodies (aPL). Clinical data on the ability of HCQ to improve pregnancy outcome in women with aPL are very limited in the available literature. Only one cohort study evaluating maternal and fetal outcome of pregnancy in patients with SLE who were exposed to HCQ was identified. Four of 14 (29 %) treated with HCQ patients had pregnancy failure, compared with six of 24 (25 %) of patients not treated with HCQ. However, the effect of HCQ was not adjusted for the use of other medications such as aspirin, heparins or steroids. Selected experts were contacted by e-mail and asked to review the summary of the evidence provided by the working group and to briefly answer each of the proposed questions. Overall, the panel of experts agreed that adding HCQ could be considered in selected cases or after failure of standard treatment with aspirin and a heparin agent. Specifically, the majority of experts considered adding HCQ in specific scenarios, such as women with previous thrombosis (either arterial and/or venous), and/or with previous ischaemic placenta-mediated complications. Prospective studies are necessary before the use of HCQ during pregnancy in women with aPL should be routinely recommended for clinical practice.
Keywords: Antiphospholipid antibodies; antiphospholipid syndrome; pregnancy